2011
DOI: 10.1007/s12687-011-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences and views of cascade screening for familial hypercholesterolemia (FH): a qualitative study

Abstract: Familial DNA cascade screening for familial hypercholesterolemia (FH) has recently been introduced in Scotland. This study investigated index patients' experiences of DNA testing and mediating cascade screening. Thirty-eight patients with a clinical diagnosis of definite or possible FH who had undergone DNA testing in the lipid clinic took part in semi-structured qualitative interviews.All patients were positive about DNA screening being undertaken by familiar and trusted clinicians within the lipid clinic. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Individuals felt it was their responsibility to discuss their results with their family and disagreed that it was the physician's responsibility to inform the participant's family. Our results are similar to patient interviews of 38 index FH cases which showed that patients were in favor of genetic testing and cascade testing (Hallowell et al 2011). This is consistent with other studies that conducted focus groups to obtain opinions about the process of communicating their results of genetic testing for cancer causing genes (Forrest et al 2003;Hallowell et al 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Individuals felt it was their responsibility to discuss their results with their family and disagreed that it was the physician's responsibility to inform the participant's family. Our results are similar to patient interviews of 38 index FH cases which showed that patients were in favor of genetic testing and cascade testing (Hallowell et al 2011). This is consistent with other studies that conducted focus groups to obtain opinions about the process of communicating their results of genetic testing for cancer causing genes (Forrest et al 2003;Hallowell et al 2005).…”
Section: Discussionsupporting
confidence: 89%
“…With consent of the proband, direct contact has been used for Familial hypercholesterolaemia in the UK and the Netherlands and is accepted by family members, 35 although a recent study finds that family members prefer indirect cascading. 36 Familial hypercholesterolaemia differs from HCM and LQTS in that diagnosis, assessment of risk and treatment are relatively uncomplicated and the disease process (coronary heart disease) widely known and understood. Ethical considerations are inherent to both approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that DNA testing undertaken within a mainstream lipid clinic is not perceived as an exceptional or anxiety provoking experience (see also Jenkins et al 2011;Hallowell et al 2011). Saukko et al (2006) similarly report that individuals undergoing screening for genetic susceptibility to thrombophilia in primary and secondary care see this procedure as generating useful information, but not as an unexceptional or unusual event.…”
Section: Revealing the Futurementioning
confidence: 98%